Mefunidone Ameliorates Bleomycin-Induced Pulmonary Fibrosis in Mice - Yuanyuan Han; Yuanyuan Han; Yuanyuan Han; Mao Jiang; Mao Jiang; Rongling He; Rongling He; Xin Lv; Xin Lv; Xiaohua Liao; Xiaohua Liao; Yijun He; et al. (Frontiers Media S.A., 2021)
Idiopathic pulmonary fibrosis (IPF) is one of the most common and devastating interstitial lung diseases with poor prognosis. Currently, few effective drugs are available for IPF. Hence, we sought to explore the role of mefunidone (MFD), a newly synthesized drug developed by our team, in lung fibrosis. In this study, MFD was found to attenuate bleomycin (BLM) -induced lung fibrosis and inflammation in mice according to Ashcroft and alveolitis scoring. The protein contents and total cell counts in bronchoalveolar lavage fluids of BLM-treated mice were also lowered by MFD. Moreover, the elevation of TGF-β/Smad2 and phosphorylation of MAPK pathways was repressed by MFD. Additionally, MFD attenuated the swelling and vacuolization of mitochondria, lowered the ratio of apoptotic cells, restored the mitochondrial membrane potential, and reversed the expression of cleaved-caspase 3, Bcl-2 and Bax. Meanwhile, the level of epithelial marker, E-cadherin, was restored by MFD, while the levels of mesenchymal markers such as Snail and vimentin were down-regulated by MFD. Besides, MFD inhibited the expression of fibronectin and α-smooth muscle actin in TGF-β treated normal human lung fibroblasts. Thus, our findings suggested that MFD could ameliorate lung fibrosis, cell apoptosis and EMT potentially via suppression of TGF-β/Smad2 and MAPK pathways.